Components of (co)variance of the weaning weight in Cuban Zebu cattle - Guerra, D.; Guill?n, A.; Espinoza, J. L.; Palacios, A.; de Luna de la Pe?a, R.; Gonz?lez-Pe?a, Dianelys; ?vila, N. (Cuban Journal of Agricultural Science, 2010)
In order to estimate the components of (co)variance of the weaning weight of Cuban Zebu cattle, there was a sample of 60 628 records of calves born between 1988 and 2006 in five genetic enterprises spread throughout the country. The data were analyzed through the Reml procedure, according to six different models alternating combinations of random genetic additive effects of the animals and maternal genetic and environmental effects. The group of contemporaries (herd-year-birth trimester-calf sex), was considered as fixed effects common to all the models; the weaning weight of the calf, as linear covariable; and the age of the mother, as linear and quadratic covariable. The results showed that, in the model ignoring the maternal effects, the heritability for the direct effects (0.31) was overestimated compared with the models considering it (H ? 0.07). The heritability for the maternal effects was similar to the direct effects (0.08) for the model of best fit. The effects of the permanent environment ranged from 0.10 to 0.13 in the models considering them. The additive genetic correlation between the direct and maternal effects had values of -0.15 and -0.29. However, their inclusion was not significant when compared with the model not including them. The outcomes indicate that the response to the selection for the genetic improvement of the weaning weight in the Cuban Zebu cattle should not be sufficiently effective. Key words: components of variances, genetic parameters, maternal effects, Cuban Zebu, weaning weight.